1969
DOI: 10.1071/ea9690157
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and survival of Merino, Corriedale, and Polwarth lambs

Abstract: The effects of year of birth, age of dam, sex, and litter size upon birth weight of lambs were examined by least squares analysis in eight flocks in Western Victoria (4 Merino, 3 Corriedale, and 1 Polwarth). Male lambs were approximately 0.8 lb heavier (P<0.01) than female lambs, single lambs about 1.6 lb heavier (P<0.01) than twin lambs. Lambs, born of 5-year-old ewes, were generally heavier (P<0.01) at birth than lambs from ewes of other ages. A general set of adjustments of birth weight for these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
3

Year Published

1982
1982
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
3
5
3
Order By: Relevance
“…On the other hand, our observations for birthweights were unexpected. The weights of singles and twins, and of ram lambs and ewe lambs, were greater than those reported by Mullaney () and, in fact, similar to those reported by Paganoni et al. () for Merino ewes aged 2–9 years.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, our observations for birthweights were unexpected. The weights of singles and twins, and of ram lambs and ewe lambs, were greater than those reported by Mullaney () and, in fact, similar to those reported by Paganoni et al. () for Merino ewes aged 2–9 years.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, our observations for birthweights were unexpected. The weights of singles and twins, and of ram lambs and ewe lambs, were greater than those reported by Mullaney (1969) and, in fact, similar to those reported by Paganoni et al (2014b) for Merino ewes aged 2-9 years. Paganoni et al (2014b) reported that mature ewes (> 3 years old) produced heavier lambs than young ewes (< 2 years old) but, as shown in the present study, with good nutritional management, there need be no disadvantage in birthweight for lambs born to very young ewes.…”
Section: Discussionsupporting
confidence: 71%
“…These differences in survival between lambs from litters of different sizes are predominantly due to differences in lamb birthweight (Hinch et al 1985(Hinch et al , 1996Kenyon et al 2007). There is a curvilinear relationship between lamb birthweight and survival in Merinos, with lamb mortality being highest at both low and high birthweights (Mullaney 1969;Atkins 1980;Hatcher et al 2009;Oldham et al 2011). Manipulating ewe nutrition during pregnancy to increase birthweight could improve survival of twin lambs , but may increase the mortality of single-born lambs due to an increase in dystocia (Hatcher et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This can result in production penalties of twin-born lambs compared with singleborn lambs. In general, Merino lambs born as twins tend to have higher mortality (Lloyd Davies 1964;Mullaney 1969;Holst et al 2002;Kleemann and Walker 2005;Oldham et al 2011), are smaller and produce less wool of slightly greater fibre diameter (Brown et al 1966;Mortimer and Atkins 1989;Lewer et al 1992; Thompson et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The differences probably would have been greater had not the caksarean group been handicapped by foster-mothering and a majority of twin births. Neonatal mortality is usually higher among twin as compared to single births ( M o d e 1954; Gunn and Robinson 1963;Mullany 1969;Hight and Jury 1970), and a higher frequency of mismothering among the fostermothered caesarean lambs was a reasonable expectation among lambs transported so soon after birth. Autopsy findings tended to support the latter contention as 71% (5 out of 7) of caesarean neonatal deaths showed lesions consistent with death from starvation and hypothermia compared with 40% (10 out of 25) in the delayed group (p-n.s.).…”
Section: Discusslonmentioning
confidence: 99%